Precompetetive cardiovascular screening in elderly wrestlers - H Asheri; A Vasheghani Farahani; V Ziaee; R Alizadeh; AR Amirbeiglou (Tehran University of Medical Sciences, 2008)
Background and Aim: Sudden death in athletes commonly is due to unknown cardiovascular diseases. Therefore many protocols have designed for screening in the world. In the last years has been spent more attention to sport in elderly athletes and the number of their competitions have been increased. The aim of this study was evaluation of risk factor of cardiovascular diseases in Iranian elderly wrestlers. Materials and Methods: All the members (60 athletes) of Iran team in Elderly Wrestling World Championship 2006 have taken census in the present study. At two sections the cardiovascular health state of them has evaluated: history taking and physical examination, electrocardiography and exercise test. All date was analyzed by SPSS version 14 and mean and standard deviation for presenting findings. Results: Sixty athletes aged 37 to 78 years (54.65±8.75) with history of exercise from 12 to 55 years (37.8±9.4) have been studied. In the history of 66.7% and in physical examination and history 75.1% athletes had at least one risk factor. Exercise test results of wrestlers were highly positive and positive in 8.6% and 5.2% respectively. Conclusion: We suggest a perfect history taking and a complete physical examination for each athlete at the first step. If you found abnormalities then noninvasive diagnostic testes such as electrocardiography, exercise test and echocardiography will be useful and informative.